Microfluidic device for separating mesenchymal stem cells from blood cells in amniotic fluid using cross-flow filtration technique. (2018) - Sabitha, B.; Muniraj, N.J.R.
Amniotic fluid, which surrounds the foetus in the womb, contains foetal cells including mesenchymal stem cells, which are able to make a variety of tissues. Women during her prenatal period elect to have the process of amniocentesis that is extracting amniotic fluid to test for chromosome defects. The extracted fluid contains mesenchymal stem cells, blood cells and tissues of the baby. The primary objective of this research is to separate the mesenchymal stem cells and the blood cell by cross-flow filtration technique. A microfluidic system is designed to separate the cell which is more effective and accurate than conventional type.